The influence of information quality in user-generated content (UGC) behavioral intention to revisit: The mediating role of destination image (a study on Lampung as a tourism object) - Hadrian, Muhammad Cyril; Ratnasari, Nissa Ghulma (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: This study aims to investigate the mediating effect of perceived destination image on the relationship between information quality in user-generated content (UGC) and behavioral intention, with a focus on the intention to revisit Lampung as a tourist destination, while extending the Stimulus-Organism-Response (SOR) model by Mehrabian and Russel. Methods: Based on the tourism context in Lampung, a total of 283 valid responses from domestic tourists were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the research hypotheses. Findings: The indirect path analysis results show that cognitive image significantly mediates the relationship between representational information quality and social information quality on behavioral intention to revisit, while affective image serves as a significant mediator in the relationship between representational information quality and contextual information quality on behavioral intention to revisit. Interestingly, this study also found that intrinsic information quality has a significant direct effect on behavioral intention to revisit. Conclusion: These findings contribute significantly to understanding how destination image influences tourists' perceptions of different types of information quality in shaping their intention to revisit, while also highlighting the complex interplay between humans and technology in the context of tourism. Novelty/Originality of this article: This study extends the Stimulus-Organism-Response (SOR) model by examining the mediating role of cognitive and affective destination images between different dimensions of UGC information quality and tourists’ behavioral intention to revisit.